SENTIMENT ANALYSIS OF ISLAMIC WAQF: EVIDENCE IN INDONESIA - AAM SLAMET RUSYDIANA (Universitas Islam Negeri Imam Bonjol Padang, 2018)
It is important to do research on public sentiment towards waqf presence in a country in order to know public response to its existence. This study aimed to determine public sentiment towards waqf in Indonesia. Data were collected from 80 articles, journals and other writings. Data were analyzed using the software Semantria as an analytical tool in the form of text. The results showed that the assessment of existence of waqf in Indonesia amounted to 66% of the community showed positive and high positive sentiment, 11% indicate negative sentiment and 23% indicates a neutral sentiment. Therefore, stakeholders need to take advantage of the awakening momentum of waqf in Indonesia so that in the future they can be a solution to the problems of social economy and the benefit of society.